2017
DOI: 10.1007/s10068-017-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extrusion with CO2 injection on physical and antioxidant properties of cornmeal-based extrudates with carrot powder

Abstract: Carrot powder and cornmeal were extruded at ratios of 0:100, 10:90, and 20:80 with and without CO injection at die temperatures of 80, 100, and 120 °C. The effects of the composition of the extrudate, die temperature, and CO injection on physicochemical and antioxidant properties of extruded products were studied. The results showed that die temperature had a significant effect on expansion ratio (ER), specific length, piece density, color, water absorption index (WAI), and water solubility index (WSI) ( < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
(41 reference statements)
3
11
0
Order By: Relevance
“…A higher yellow pea extrudate density with CO 2 injection compared to N 2 injection and conventional extrusion may be due to the differences in the solubility of CO 2 as compared to N 2 (approximately 1.5–2 orders of magnitude difference in their solubility in water at ambient temperature and pressure [Gevantman, ]). A higher extrudate density with CO 2 injection was also seen in barley flour supplemented and vitamin fortified corn extrudates (Bilgi Boyaci et al, ; Masatcioglu, Gokmen, et al, ; Masatcioglu, Yalcin, et al, ) at a relatively low temperature (i.e., 80 °C) and in carrot powder supplemented cornmeal extrudates (Samard et al, ) at a temperature similar (i.e., 130 °C) to what is used in this study. A decrease in extrudate density and an increase in expansion index, although not statistically significant, in the presence of N 2 gas injection were also reported for puffed yellow pea snacks at the same temperature as in this study (Koksel & Masatcioglu, ).…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…A higher yellow pea extrudate density with CO 2 injection compared to N 2 injection and conventional extrusion may be due to the differences in the solubility of CO 2 as compared to N 2 (approximately 1.5–2 orders of magnitude difference in their solubility in water at ambient temperature and pressure [Gevantman, ]). A higher extrudate density with CO 2 injection was also seen in barley flour supplemented and vitamin fortified corn extrudates (Bilgi Boyaci et al, ; Masatcioglu, Gokmen, et al, ; Masatcioglu, Yalcin, et al, ) at a relatively low temperature (i.e., 80 °C) and in carrot powder supplemented cornmeal extrudates (Samard et al, ) at a temperature similar (i.e., 130 °C) to what is used in this study. A decrease in extrudate density and an increase in expansion index, although not statistically significant, in the presence of N 2 gas injection were also reported for puffed yellow pea snacks at the same temperature as in this study (Koksel & Masatcioglu, ).…”
Section: Resultssupporting
confidence: 62%
“…It has been previously reported that hardness and crispiness have an inverse relationship (Oliveira et al, ). This trend is heavily dependent on die temperature, screw speed, and moisture content (Ding et al, ; Lohani & Muthukumarappan, ; Samard et al, ). The selected temperature, screw speed, and moisture content in this study did not allow this trend to be observable when comparing the conventional and physical blowing agent‐assisted extrudates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations